Long-Term Stability Metrics of Photoelectrochemical Water Splitting - Vanka, Srinivas; Zeng, Guosong; Deutsch, Todd G.; Toma, Francesca Maria; Mi, Zetian (Frontiers in Energy Research, 2022)
Photoelectrochemical (PEC) water splitting, one of the most promising technologies for clean hydrogen generation, has drawn considerable attention over the past few decades. Achieving simultaneous highly efficient and stable unassisted PEC water splitting has been the “holy grail” in clean and renewable fuel generation. State-of-the-art photoelectrodes have shown relatively high efficiencies (∼10–20%). Still, their stability is limited due to photoelectrode chemical instability, electrolyte resistance, mass transfer issues, and an often unoptimized experimental setup. In this work, we present a framework and a set of protocols for conducting long-term stability experiments and further provide details on several critical factors such as light source calibration, choosing the right counter electrode, the configuration of the PEC cell, and photoelectrode sample preparation.